2014
DOI: 10.1186/1465-9921-15-16
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone inhibits fibrocyte accumulation in the lungs in bleomycin-induced murine pulmonary fibrosis

Abstract: BackgroundBone marrow-derived fibrocytes reportedly play important roles in the pathogenesis of idiopathic pulmonary fibrosis. Pirfenidone is an anti-fibrotic agent; however, its effects on fibrocytes have not been investigated. The aim of this study was to investigate whether pirfenidone inhibits fibrocyte pool size in the lungs of bleomycin-treated mice.MethodsBleomycin (100 mg/kg) was infused with osmotic pumps into C57BL/6 mice, and pirfenidone (300 mg/kg/day) was orally administered daily for 2 wk. The lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 45 publications
6
64
1
1
Order By: Relevance
“…The other two groups were Con A + PFD treated where mice were pretreated orally with PFD at two different doses (200, 300 mg/kg, oral) for 5 days. The PFD doses were selected based on previous studies …”
Section: Methodsmentioning
confidence: 99%
“…The other two groups were Con A + PFD treated where mice were pretreated orally with PFD at two different doses (200, 300 mg/kg, oral) for 5 days. The PFD doses were selected based on previous studies …”
Section: Methodsmentioning
confidence: 99%
“…In humans, both CXCL8 and CCL2 concentrations were found to be increased in blood (Ziegenhagen et al, 1998a;Suga et al, 1999;Fujiwara et al, 2012) and bronchoalveolar lavage fluid (BALF) (Capelli et al, 2005;Antoniou et al, 2006;Baran et al, 2007) of IPF patients compared with healthy volunteers and correlated with lung function (Capelli et al, 2005;Emad and Emad, 2007;Martina et al, 2009;Vasakova et al, 2009), disease progression (Ziegenhagen et al, 1998b;Totani et al, 2002), and outcome (Shinoda et al, 2009;Richards et al, 2012). Furthermore, several studies suggested an involvement of the chemokine CCL2 in the pathogenesis of IPF, notably through its action on resident pulmonary fibroblast and circulating fibrocytes, promoting the generation of abundant extracellular matrix in the lungs (Gharaee-Kermani et al, 1996;Phillips et al, 2004;Moore et al, 2005;Inomata et al, 2014). Such strong evidence involving CXCL8 in the pathogenesis of the disease are lacking, although this chemokine is thought to act as a pro-fibrotic factor in IPF via the promotion of exacerbated angiogenesis (Strieter et al, 2002;Rosenkilde and Schwartz, 2004;Antoniou et al, 2006;Martina et al, 2009;Cui et al, 2010).…”
Section: Cxcl8 and Ccl2 Concentrationsmentioning
confidence: 99%
“…It has been evaluated in multicenter, randomized, double-blind, placebo-controlled clinical trials conducted in Japan and the USA for the treatment of IPF and has been shown to have an acceptable tolerability and safety profile (Azuma et al, 2005;Kreuter, 2014;Noble et al, 2011). The antifibrotic activity of pirfenidone is believed to result mainly from reduced synthesis and accumulation of collagen in lung tissue and downregulation of the pulmonary growth factor, transforming growth factor-b1 (Inomata et al, 2014).…”
Section: Introductionmentioning
confidence: 98%